Methoxyphenols in Arctic seawater - PADOAN, SARA; BARBARO, ELENA; ZANGRANDO, Roberta; KARROCA, ORNELA; BARBANTE, Carlo; GAMBARO, Andrea (Società Chimica Italiana, 2016)
METHOXYPHENOLS IN ARCTIC SEAWATER S. Padoan 1, E. Barbaro 1,2, R. Zangrando2, O. Karroca1, C. Barbante2, A. Gambaro1,2 1 Department of Environmental Sciences, Informatics and Statistics, University of Venice, Ca' Foscari, Via Torino 155, 30170 Venezia, Mestre, Italy 2 Institute for the Dynamics of Environmental Processes CNR, Via Torino 155, 30170 Venezia, Mestre, Italy Methoxyphenols are organic and semi-volatile compounds that are used as specific biomarkers of combustion events. These compounds are able to provide information about the type of combusted biomass [1]. Recently, several studies [2] have highlighted that the presence of methoxyphenols in polar areas are attributable not only to biomass burning but also to local marine sources. The purpose of the present work was to determine free phenolic compounds in both dissolved and particulate fractions in Arctic seawater samples. We analyzed 67 samples of coastal seawater collected near the coast line of Kongsfjord during the Arctic sampling campaign 2015. The quantitative determination has been performed using a HPLC-MS/MS method developed by Zangrando et al. [3]. Vanillic acid, vanillin, p-coumaric acid, syringic acid, isovanillic acid, homovanillic acid, syringaldehyde, acetosyringone and acetovanillone were determined. In dissolved phase there was a higher concentration of methoxyphenols than in the particulate fraction. The most abundant compounds in our samples were vanillic acid, vanillin, acetovanillone and p-coumaric acid. [1] Zennaro, P., et al., Fire in ice: two millennia of boreal forest fire history from the Greenland NEEM ice core. Climate of the Past, 2014. 10(5): p. 1905-1924. [2] Zangrando, R., et al., Levoglucosan and phenols in Antarctic marine, coastal and plateau aerosols. Science of The Total Environment, 2016. 544: p. 606-616. [3] Zangrando, R., et al., Molecular markers of biomass burning in arctic aerosols. Environ Sci Technol, 2013. 47(15): p. 8565-74.